PERFORMANCE FORM OF PEPE BAINE DANCE IN SANGGAR SIRAJUDDIN KABUPATEN GOWA - Jamilah, Jamilah; Wahyuni, Sri (Sembadra, Journal of Arts and Education Studies, 2020)
Pepe-pepe Baine dance at the Sirajuddin Studio in Gowa Regency, has a difference when compared to the Pepe-pepe dance in Paropo, Makassar city in terms of the concept and form of presentation. The Pepe-pepe Baine dance is conceptually danced by female dancers according to its name, namely baine (female) with an even number of dancers or in pairs. The property used is a small torch that is lit when the show progresses. The uniqueness of the Pepe-pepe Baine dance is that it involves the audience in the show to feel the torch lit with a burning fire, but the audience does not burn or feel the heat of the fire. The climax is when the dancer performs a very bold attraction by spraying kerosene which is released from the mouth of the dancers, adding to the big flames that are created. This Pepe-pepe Baine dance performance is usually displayed at pick-up events, entertainment at weddings. The current development of this dance can be performed at any time according to the demand. Keywords: Pepe-pepe, Baine, Social Culture.